Skeletal manifestation of tuberculosis in a late medieval anthropological series from Serbia - Lovász, Gabriella (Acta Biologica Szegediensis, 2010)
The aim of this study is to present the results of the paleopathological investigation of tuberculosis (TB) in the late medieval (16th-17th c. AD) anthropological series of the Zombor-Repülőtér site from Serbia. The paleopathological analysis of TB was carried out in two phases during which macromorphological methods were used. The first phase of the investigation focused on classical/advanced stage skeletal TB alterations. In the second phase the atypical/early-stage TB lesions and 3 stress factors were also taken into consideration. The first phase of the investigation revealed two cases of tuberculosis in the series. However, in the second phase of the investigation additional 32 probable TB cases were recognized. The association of different tuberculous lesions (both classical and atypical/early stage alterations) as well as stress indicators were found in most of these cases, which rises the probability of the diagnosis of tuberculosis. The remarkable difference between the prevalence in the two phases of the investigation shows that the detection of diagnostic criteria related to atypical/early-stage tuberculosis raises the possibility of identifying TB cases.